2016
DOI: 10.1021/acs.biochem.6b00093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Spiroiminodihydantoin Lesion on Nucleosome Stability and Positioning

Abstract: DNA is constantly under attack by oxidants, generating a variety of potentially mutagenic covalently modified species, including oxidized guanine base products. One such product is spiroiminodihydantoin (Sp), a chiral, propeller-shaped lesion that strongly destabilizes the DNA helix in its vicinity. Despite its unusual shape and thermodynamic effect on double-stranded DNA structure, DNA duplexes containing the Sp lesion form stable nucleosomes upon being incubated with histone octamers. Indeed, among six diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
(165 reference statements)
0
7
0
Order By: Relevance
“…For example, the presence of dGh and dSp could influence the thermal stability and folding of the G-quadruplex, 291 and dSp lesions could disturb the structure of duplex DNA and affect nucleosome positioning. 292 dGh and dSp lesions have been detected in E. coli 197 and in mice, 131 though further studies are needed for systematically assessing their formation and repair in mammals.…”
Section: Implications Of Oxidative Stress-inducedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the presence of dGh and dSp could influence the thermal stability and folding of the G-quadruplex, 291 and dSp lesions could disturb the structure of duplex DNA and affect nucleosome positioning. 292 dGh and dSp lesions have been detected in E. coli 197 and in mice, 131 though further studies are needed for systematically assessing their formation and repair in mammals.…”
Section: Implications Of Oxidative Stress-inducedmentioning
confidence: 99%
“…In the viewpoint that 8-oxo-dG is produced at high frequencies and that it is more readily oxidized than dG, the major oxidation products of 8-oxo-dG, i.e., dGh and dSp, may bear a significant impact on cellular functions. For example, the presence of dGh and dSp could influence the thermal stability and folding of the G-quadruplex, and dSp lesions could disturb the structure of duplex DNA and affect nucleosome positioning . dGh and dSp lesions have been detected in E. coli and in mice, though further studies are needed for systematically assessing their formation and repair in mammals.…”
Section: Implications Of Oxidative Stress-induced Dna Lesions In Huma...mentioning
confidence: 99%
“…Recently, the Núñez and Jamieson groups found that the Sp lesion would have minor effects on the stability and positioning of nucleosomal DNA. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the groups of Nuńẽz and Jamieson found that the Sp lesion would have minor effects on the stability and positioning of nucleosomal DNA. 22 Interestingly, Sp exists as two stable diastereomers, (+)-(S)-Sp and (−)-(R)-Sp, that originate from the stereocenter formed by the junction of the two heterocyclic rings of Sp (Figure 1A). For the sake of brevity, (+)-(S)-Sp and (−)-(R)-Sp are herein abbreviated as (S)-Sp and (R)-Sp, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation